Multidimensional Integral Equations and Inequalities - Pachpatte, B.G.; SpringerLink (Online service) (Paris : Atlantis Press, 2011)
Since from more than a century, the study of various types of integral equations and inequalities has been focus of great attention by many researchers, interested both in theory and its applications. In particular, there exists a very rich literature related to the integral equations and inequalities and their applications. The present monograph is an attempt to organize recent progress related to the Multidimensional integral equations and inequalities, which we hope will widen the scope of their new applications. The field to be covered is extremely wide and it is nearly impossible to treat all of them here. The material included in the monograph is recent and hard to find in other books. It is accessible to any reader with reasonable background in real analysis and acquaintance with its related areas. All results are presented in an elementary way and the book could also serve as a textbook for an advanced graduate course. The book deserves a warm welcome to those who wish to learn the subject and it will also be most valuable as a source of reference in the field. It will be an invaluable reading for mathematicians, physicists and engineers and also for graduate students, scientists and scholars wishing to keep abreast of this important area of research.
Integral equations in two variables -- Integral inequalities and equations in two and three variables -- Mixed integral equations and inequalities -- Parabolic-type integrodifferential equations -- Multivariable sum-difference inequalities and equations.
Keywords: Mathematics; Global analysis (Mathematics).; Integral equations; Mathematics; Analysis; Integral Equations